Profitability Analysis of Selected Private Sector Banks - Anil Kalubhai Vanvi (Journal La Bisecoman, 2022)
The fundamental objective of this study is to acquire an understanding of the profitability of the many private sector banks that were selected for the purpose of investigation. A lottery was used as the fundamental method of random sampling for the purpose of this inquiry. The sample unit for this investigation will consist of five banks that were chosen by the researcher. The investigation will take place over the course of a period of five calendar years, commencing in 2017 and concluding in 2021. The researcher made use of a variety of accounting techniques, such as profitability ratios, as well as statistical methods, such as one-way analysis of variance; the findings are discussed further down in this section.